Hypotrichosis‐lymphedema‐telangiectasia‐renal defect associated with a truncating mutation in the SOX18 gene. (16th April 2014) - Moalem, S.; Brouillard, P.; Kuypers, D.; Legius, E.; Harvey, E.; Taylor, G.; Francois, M.; Vikkula, M.; Chitayat, D.
Abstract : SOX18 mutations in humans are associated with both recessive and dominant hypotrichosis–lymphedema–telangiectasia syndrome (HLTS). We report two families with affected children carrying a SOX18 mutation: a living patient and his stillborn brother from Canada and a Belgian patient. The two living patients were diagnosed with HLTS and DNA analysis for the SOX18 gene showed that both had the identical heterozygous C > A transversion, resulting in a pre‐mature truncation of the protein, lacking the transactivation domain. Both living patients developed renal failure with severe hypertension in childhood for which both underwent renal transplantation. To our best knowledge this is the first report of renal failure associated with heterozygous mutations in the SOX18 gene. We conclude that this specific mutation results in a new, autosomal dominant condition and propose the acronym HLT‐renal defect syndrome for HLTRS.